2021
DOI: 10.1111/jne.12957
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone receptor in dopaminergic neurones regulates stress‐induced prolactin release in male mice

Abstract: Arcuate nucleus (ARH) dopaminergic neurones regulate several biological functions, including prolactin secretion and metabolism. These cells are responsive to growth hormone (GH), although it is still unknown whether GH action on ARH dopaminergic neurones is required to regulate different physiological aspects. Mice carrying specific deletion of GH receptor (GHR) in tyrosine hydroxylase (TH)‐ or dopamine transporter (DAT)‐expressing cells were produced. We investigated possible changes in energy balance, gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
0
6
1
Order By: Relevance
“…Therefore, GH action in CRH neurons does not modulate the acute responses to stress. In contrast to our findings, GHR signaling in dopamine neurons regulates prolactin release during restraint stress [ 32 ]. GHR ablation in VMH neurons acutely impairs the counterregulatory response induced by 2DG or insulin [ 5 ], which is another form of metabolic stress.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, GH action in CRH neurons does not modulate the acute responses to stress. In contrast to our findings, GHR signaling in dopamine neurons regulates prolactin release during restraint stress [ 32 ]. GHR ablation in VMH neurons acutely impairs the counterregulatory response induced by 2DG or insulin [ 5 ], which is another form of metabolic stress.…”
Section: Discussioncontrasting
confidence: 99%
“…Plasma samples were obtained after centrifuging blood collected from the tail vein using heparinized capillaries (75 mm length and 1.5 mm diameter). To determine restraint-stress-induced corticosterone secretion, mice at 09:00 a.m. were physically restrained for 120 min in 50 mL polypropylene centrifuge tubes, containing holes of 0.4 cm diameter to breathe, as previously described [ 32 ]. A small cut in the tail tip was performed to allow blood collection using heparinized capillaries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Auriemma et al 32 reported that fasting insulin and insulin selective index in hyperprolactinemic male patients have been found to significantly improve after treatment with dopamine agonist. Basic experiments showed that in female mice, cholesteryl ester transfer protein, a lipid shuttling protein, is essential for HDL-C metabolism, and cholesteryl ester transfer protein is estrogen-dependent 33 ; in male mice, the presence of growth hormone is essential for dopaminergic neurons to secrete prolactin, and growth hormone influences blood glucose levels 34 . Consequently, we found the negative correlation between serum HDL-C levels and prolactin levels in female subjects, and the positive correlation between FBS levels and prolactin levels in male subjects, which may be due to the existence of sex differences in prolactin secretion and metabolic processes.…”
Section: Discussionmentioning
confidence: 99%